The Prisoner Assimilation Policy from a Proportionality Perspective: A Critical Analysis of Rights, Power, and Social Transformation - Djian Fadilla; Surya Perdana (Abdurrauf Social Science, 2026)
This study examines the problems of the inmate assimilation policy that creates tension between the protection of prisoners' rights and the interests of public security in the perspective of the principle of proportionality. The main problem lies in the lack of optimal application of the principle of proportionality in assimilation policies, especially in the context of emergency conditions that affect the direction of policies and their implementation in the field. The purpose of this study is to critically analyze how the principle of proportionality is applied, as well as identify the influence of power relations on the formation and implementation of assimilation policies and their implications for social transformation. This research uses a literature method with a normative-critical approach through analysis of relevant laws and regulations, policy documents, and academic literature. The data used includes primary sources in the form of regulations and policies, as well as secondary sources in the form of books, scientific journals, and the results of previous research. The results of the study show that the application of the principle of proportionality in assimilation policies is not consistent and tends to be influenced by power dynamics and emergency situations. In conclusion, a reconstruction of assimilation policies that are more proportionate, transparent, accountable, and oriented towards the balance of justice is needed.